tert-Butyl N-[(S)-1-hydrazinecarbonyl-2-hydroxyethyl]carbamate - Pinheiro, A.C.; de Souza, M.V.N.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(8)H(17)N(3)O(4), the dihedral angle between the hydrazinecarbonyl and carbamate groups is 44.94 (12)degrees, and the carbonyl groups are anti to each other. In the crystal, the hydroxy group forms an O-H center dot center dot center dot N(a) (a = amine) hydrogen bond and each of the four N-H atoms forms an N-H center dot center dot center dot O hydrogen bond; the hydrazinecarbonyl O atom accepts two such bonds. This results in two-dimensional arrays in the ab plane, mediated by the hydrogen bonding, sandwiched by tertbutyl groups.